Méthodologie de mise en place d’une Trame verte urbaine : le cas d’une communauté d’agglomération, Plaine Commune - Marine Linglart; Sylvain Morin; Magali Paris; Philippe Clergeau (Cybergeo, 2016)
The “Grenelle de l’Environnement” forum outlined the importance of taking into account the dispersion of species across territories and therefore proposed the identification and protection of ecological networks with reservoirs of biodiversity and connecting corridors: the “Trames vertes et bleues” (TVB). In urbanized areas, these TVB are difficult to define not only because of the mosaic of land uses and the importance of the barriers constituted by built elements, but also because of land pressures and urban practices. The approach cannot be reduced to a naturalist study. The sustainability of a green city network is highly dependent on its perception and acceptance by the inhabitants. In this context and at the request of local communities, we have been led to propose plans of TVB which gradually strengthened an interdisciplinary methodology. Through the example of Plaine Commune’s TVB plan(north of Paris), we deliver here this methodology based on a complementarity of diagnoses (regarding ecology, landscapes, projects, green space practices) and a consultation with main actors. This method results in a map of global actions (conception of local objectives, landscape guidelines...) and local actions (space management advice, projects development...).